Pengaruh Konsentrasi Carbopol 940 Sebagai Gelling Agent Terhadap Stabilitas Fisik Sediaan Gel Lidah Buaya (Aloe Vera) - Nur Ain Thomas; Robert Tungadi; Faramita Hiola; Multiani S. Latif (Indonesian Journal of Pharmaceutical Education, 2023)
Carbopol 940 is a gelling agent that is very communly used in cosmetic production because of its high compatibility and stability, and it is non-toxic when applied to the skin and it spreads on the skin more easilym gels are semi solid preparations that contain a gel-forming agent which gives stiffiness to collodial solutions or dispersions used for external use on the skin, gel preparations are widely chosen because they are very easy to apply ( easily smeared, absorbed, and cleaned) and more attractive (transparent) compared to the other topical preparations. the purpose of this study was to determine the effect of carbopol concentration 940 as a gelling agent on the physical stability of aloe vera gel preparations. this study began with optimization of the carbopol 940 gel base then the preparation formulation used 50% aloe vera extract, 0,5% carbopol 940 F1, 1 % F2, 2% F3, 10 % propylene glycol, 10% glycerine, 0,1% dm dm hydantoin and sufficient aquadest, afterward the evaluation of the preparation included organoleptic, observations, homogeneity tests, pH tests, spreadability tests, adhesion tests and viscosity tests. carbopol 940 was depeloped using co-free water. gel preparations were 0,5%, 1%, and 2%. the results showed that the thrid formulation (F3) with a concentration of 2% fulfilled the physical evaluation requirements for organoleptic, spreadability, adhesion, viscosity, pH and homogeneity tests.